Um olhar sobre a vida de idosas religiosas : sua funcionalidade e qualidade de vida - Klein, Bruna (2014)
The general objective of the present study was to evaluate the functionality and life quality of elderly religious and characterize their health conditions. It is a transversal study of analytic and descriptive character, with quantitative approach. The criteria for inclusion were all the elderly sisters above 60 years of age, belonging to the congregation of a city in South Brazil, who still were in cognitive and physical health conditions and thus able to participate in the research. The data collection was made between January and June 2013, by the researcher, using a questionnary she herself had structured. Part I - personal data and health conditions. Part II - evaluation of the functional capability using the scale of Katz, which evaluates the individual in six basic tasks of daily life (bath, clothing, hygiene, transfers, continence, nourishment). Part III the quality of life scale WHOQOL OLD, is a questionnaire with questions referring to the loss of senses, with freedom to participate in activities, control of the own future. Parts of the results were compiled in two scientific productions, both attached to the present text. The first one is entitled Functionality and Life Quality of Elderly Religious ; the second scientific production has the title Life Quality of Sedentary Elderly Religious . Data were evaluated according to the tests of Variance Analysis (ANOVA), the Chi-Square Test of adherence, as well as Pearson s Test of Correlation. The results of the studies show the need of further studies with elderly religious in the area of aging